Comparative analysis of acoustic therapies for tinnitus treatment based on auditory event-related potentials - Alonso-Valerdi, Luz M.; Ibarra-Zárate, David I.; Torres-Torres, Alma S.; Zolezzi, Daniela M.; Naal-Ruiz, Norberto E.; Argüello-García, Janet (Frontiers in Neuroscience, 2023)
The aim of the present study is to propose a methodology based on Auditory Event-Related Potentials (AERPs) to evaluate the effectiveness of four acoustic therapies for tinnitus treatment. The acoustic therapies were: (1) tinnitus retraining therapy (TRT), (2) auditory discrimination therapy (ADT), (3) therapy for enriched acoustic environment (TEAE), and (4) binaural beats therapy (BBT). In addition, relaxing music was included as a placebo for both: tinnitus sufferers and healthy individuals. To meet this aim, 103 participants were recruited, 53% were females and 47% were males. All the participants were treated for 8 weeks with one of these five sounds, which were moreover tuned in accordance with the acoustic features of their tinnitus (if applied) and hearing loss. They were electroencephalographically monitored before and after their acoustic therapy, and wherefrom AERPs were estimated. The sound effect of acoustic therapies was evaluated by examining the area under the curve of those AERPs. Two parameters were obtained: (1) amplitude and (2) topographical distribution. The findings of the investigation showed that after an 8-week treatment, TRT and ADT respectively achieved significant neurophysiological changes over somatosensory and occipital regions. On one hand, TRT increased the tinnitus perception. On the other hand, ADT redirected the tinnitus attention, what in turn diminished the tinnitus perception. Tinnitus handicapped inventory outcomes verified these neurophysiological findings, revealing that 31% of patients in each group reported that TRT increased tinnitus perception, but ADT diminished it. This study raises the possibility to assign acoustic therapies by neurophysiological response of patient.